91 Impact of Neoadjuvant Androgen Deprivation Therapy (NADT) on Erectile Function Recovery (EFR) after Radical Prostatectomy (RP). Issue 1 (1st April 2022) - Flores Martinez, J; Jenkins, LC; Benfante, N; Touijer, K; Mulhall, JP
ABSTRACT: Introduction: NADT has gained increasing recognition in the management of men with high risk disease prior to RP No large study to date has examined EFR in such patients Objective: We aimed to define such outcomes with this analysis. Methods: Men who underwent NADT pre-RP with ≥2-year follow-up post-RP constituted the study population. Patients who received ADT post-RP and radiation therapy pre and post-RP were excluded. Demographics, comorbidity, hormone and pathological parameters were recorded. EFR was assessed using the International Index Erectile Function-Erectile Function Domain (EFD) score. Predictors of EFR were analyzed using logistic regression models. Results: 260 men were analyzed. Mean age of 63.6 ± 7.1 years. 11.2% had diabetes, 55% hypertension, 54.2% dyslipidemia, and 16.9% and 5.8% history of sleep apnea and coronary artery disease respectively. Regarding smoking history, 6.9% was current smoker, and 33.1% former smoker. Baseline testosterone was 352.1 ± 225.9 ng/dL, PSA 9.6 ± 8.4 ng/mL, and median EFD score 24 (IQR = 14-30). Median Gleason sum was 7 (IQR = 7-9). 43.4% patients had bilateral nerve sparing status (NSS), and 34% unilateral. 13.1% received NADT. Median duration of NADT was 1 (IQR = 1-3) months. At 2 years post-RP, median EFD was 7 (IQR = 3-22) for men without NADT and 4 (IQR = 2-13) for men with NADT; 8.8% and 21.2% had an EFD score ≥ 24 in men with and without NADT. 73.5% and 55.3% had an EFD score ≤ 10 in men with and without NADT. Conclusions: Men with NADT had lower EFR at 2 years post-RP, however NADT did not predict EFR in our cohort. Disclosure: No